Identification and Control Model for Pest Organisms in Cabbage Plants - Nikolas Nik; Aloysius Rusae; Oktovianus Tasekab; Florenci Bano; Yanti Oktofiana Pais; Yohanes Tanii (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of the research is to identify pests according to family and find out the types and concentrations of vegetable pesticides that are effective for controlling pests on cabbage plants using vegetable pesticides, using net sweeping and using light on cabbage plants. This research activity included 2 stages. The first stage is to identify pests on cabbage plants using the insect net method and light lamps, taking insects directly every 7 days of observation. The number of pest insects obtained is recorded and identified based on their family. The second stage is the application of vegetable pesticides and the frequency of spraying on the intensity of pest and disease attacks on cabbage plants. This research is a factorial experimental study using a randomized block design (RAK) method consisting of 2 factors with the first factor being the type of vegetable pesticide consisting of 4 levels, namely (F0) control, (F1) neem, (F2) Annona and (F3) Widuri. The second factor is that the spraying frequency varies, consisting of 3 levels, namely (K1) 3x spraying (K2), 5x spraying and (K3) 7x spraying. Parameters observed included plant height, number of leaves, plant fresh weight, percentage of pest attack intensity and incidence of cabbage disease. Data were analyzed using the Duncan Multiple Range Test (DMRT) 5%. The research results show that the insect pests identified are the families Pyralidae, Plutelidae, Acrididae, Noctuidae and Aphididae. The results of testing a pesticide that is effective in controlling insects is neem pesticide with a spraying time of 7 times which can reduce the intensity of pest and disease attacks on cabbage plants